2017
DOI: 10.1002/2017jc013333
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Ganges‐Brahmaputra River Plume by the Indian Ocean Dipole and Eddies Inferred From Satellite Observations

Abstract: The Bay of Bengal receives large amounts of freshwater from the Ganga‐Brahmaputra (GB) river during the summer monsoon. The resulting upper‐ocean freshening influences seasonal rainfall, cyclones, and biological productivity. Sparse in situ observations and previous modeling studies suggest that the East India Coastal Current (EICC) transports these freshwaters southward after the monsoon as an approximately 200 km wide, 2,000 km long “river in the sea” along the East Indian coast. Sea surface salinity (SSS) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(109 citation statements)
references
References 42 publications
16
93
0
Order By: Relevance
“…Several studies reported that SMAP is able to retrieve SSS with some confidence in coastal regions within 500-1000 km offshore in many places around the globe [11][12][13][14][15][16][17][18][19]. The present study adds another region to that list: the Red Sea.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Several studies reported that SMAP is able to retrieve SSS with some confidence in coastal regions within 500-1000 km offshore in many places around the globe [11][12][13][14][15][16][17][18][19]. The present study adds another region to that list: the Red Sea.…”
Section: Discussionmentioning
confidence: 78%
“…and histograms were calculated for each SMAP product for the collocated datasets to assess SMAP performance in the North Indian Ocean in both the spatial and temporal domains. These statistics are generally used in studies evaluating satellite salinity observations [1,3,8,9,12,13,[16][17][18]21,61].…”
Section: Collocation Between Smap and In Situ Observations And Statismentioning
confidence: 99%
“…SSS is a key parameter influencing the ocean circulation through its effect on density but is also a tracer of air‐sea freshwater fluxes and ocean dynamics. Satellite missions have revealed that SSS anomalies associated with eddies can be monitored for months near river outflows (Fournier, Vandemark, et al, ; Fournier, Vialard, et al, ) and large anomalies can be seen in the tropical Pacific Ocean following El Niño and La Niña events (Hasson et al, , ). Studies have also shown that remotely sensed SSS in the tropical Pacific Ocean be used to trace mesoscale features such as tropical instability waves (Lee et al, ; Melnichenko et al, ; Yin et al, ) and heavy rainfall associated with large convective cells in the ITCZ (Supply et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Meridional SSS gradients are large in October along 85°E in 2015, along 88°E in 2016, and along 90°E in 2017, and large zonal SSS gradients are noticed at 18°N in 2015 and 2017. The equatorward flowing East India Coastal Current (EICC) advecting northern low-salinity waters southward is weaker in October 2015(Figure 1d) in association with the pIOD and is stronger up to 15°N in October 2016 and 2017(Figures 1e and 1f) in association with the nIOD(Fournier et al, 2017;Subrahmanyam et al, 2011). The observed SMAP SSS in the northern BoB in October 2015 (very low SSS, <30.0 psu) and October 2016 (relatively high SSS, >32.0 psu over a larger area) correspond to the impact of the pIOD and nIOD events(Akhil et al, 2014;Chaitanya et al, 2015;Subrahmanyam et al, 2011).…”
mentioning
confidence: 99%